Gastro-oesophageal reflux is more prevalent in Western dyspeptics: a prospective comparison of British and South-East Asian patients with dyspepsia - Mahadeva, S.; Raman, M.C.; Ford, A.C.; Follows, M.; Axon, A.T.R.; Goh, Khean Lee; Moayyedi, P. (Blackwell Publishing, 2005)
GERD is more common in British compared with South-East Asian dyspeptic patients suggesting that race and/or western lifestyle are important risk factors.